Control of cross-linking and reactions in one-step dispersion polymerization toward particles with combined anisotropies. Issue 15 (4th April 2016) - Liu, Yanan; Jiang, Kun; Ma, Yuhong; Liu, Lianying; Yang, Wantai
Abstract : Particles with a combination of anisotropies in morphology, surface roughness, structure and composition are synthesized by one-step dispersion polymerization. Abstract : Previously, it was a challenge to develop a direct and convenient synthetic means for production of anisotropic particles, formation of structures (core–shell, cavity, hollow, etc. ) and functionalization of domains all at once. Herein, we present a simple one-step dispersion polymerization (Dis.P) approach to synthesize particles with a combination of anisotropies in morphology, surface roughness, structure and composition. This approach needs no delayed addition of agents, and is of comparable simplicity to the preparation of conventional spherical particles. A cross-linker of dimethacryloyloxybenzophenone (DMABP) is added at the beginning of Dis.P of styrene (St). Evolution of monomer conversion, particle gel content and morphology during Dis.P indicates that DMABP is consumed early and rapidly, creating a high cross-linking of a growing particle at a low conversion, thus inducing phase separation and producing snowman- or dumbbell-like particles which contain a firstly cross-linked, coarse growing particle domain (G domain) and an uncross-linked or subsequently cross-linked, smooth, new domain (N domain). The size, surface roughness, structure and composition of the domains are tuned by initially adding various amounts of DMABP and a low amount of functional monomers. Due to the quick reaction of hydrophilic 4-vinylpyridine (4-VP), glycidyl methacrylate (GMA) or methacrylic acid (MAA), the G domain is enriched with pyridyl, epoxy or carboxyl groups, as detected by XPS and EDS. Through the delayed reaction of monomers containing alkynyl groups (–CC–), the N domain is enriched with –CC– groups, and the core–shell (cross-linked) structure is formed. With aids of thiols added during Dis.P, SH– or fluorine-containing groups are primarily incorporated on the N domain, and the porous, cavity or hollow structure of the N domain is generated due to phase separation between polystyrene (PSt) and the polymer produced by the click reaction. On adding two functional monomers (MAA and monomer containing –CC– groups), various functional groups enrich G and N domains, respectively, owing to the sequential reactions of monomers.